Efficacy of Video -based Teaching Versus Lecture cum Demonstration Regarding Compression Only Life Support: A Multi-Arm Randomized Control Study - Kulkarni Sadhana Sudhir; Joshi Bhavna Pramod; Kachare Avinash Prabhakarrao; Bidve Junneshwar Laxman; Gunjale Yashoda Sitaram (National Board of Examinations Journal of Medical Sciences, 2025)
Introduction: In sudden cardiac arrests, early initiation of chest compression by bystanders increases the survival rate by two to three times. Hence training lay population in COLS is imperative. However, due to limited resources, alternate training modes for COLS must be explored. Aim: To evaluate efficacy of video-based teaching compared to traditional lecture-cum-demonstration (LCD) for teaching COLS. Material & Methods: A multi-arm parallel-group non-inferiority randomized control study was conducted among 85 first year physiotherapy students. The participants were randomly allocated to three arms. Traditional LCD was control while video song (VS) and video-based LCD (VLCD) were test arms. Post intervention, psychomotor skill gain as well as cognitive assessment was done using objective methods. Results: The mean age of the 85 participants was 19.04 years (S.D.= 0.932; Range: 17 to 22). Of these, 63 (74.11%) were females and 22 (25.88%) were males. One way ANOVA for psychomotor assessment showed no statistically significant difference between the 3 groups (F value: 1.918, p = 0.153). One way ANOVA showed that there is no statistically significant difference in knowledge gained among the three groups (F value: 0.056, p = 0.946). Conclusion: Skill and knowledge acquisition using VS and VLCD is not as good as LCD.